Dinâmica territorial dos Sistemas Agroflorestais em áreas de várzea e terra firme, na Amazônia oriental - Wagner Luiz Nascimento do Nascimento; Roberta de Fátima Rodrigues Coelho; François Laurent (Confins)
The agro-ecological transition in the Amazon is a crucial issue for improving the living conditions of rural populations and protecting the environment. Agroforestry systems seem to offer a sustainable alternative as part of this transition. This article analyzes the influence of production dynamics on the agricultural development of two municipalities in the Eastern Amazon, based on their historical and cultural trajectories, in order to understand the role played by territorial specificities in the establishment and dissemination of Agroforestry Systems (SAFs). The research was carried out in the municipalities of Igarapé Miri and Tomé Açu, using exploratory and descriptive research of a qualitative and quantitative nature, interviews with family farmers and observations of their properties. The results show production dynamics specific to each region, influenced by the economic cycles and crises they have been through. This was achieved through SAFs. The analysis shows that the adoption of SAFs in the territories depends on the biophysical environment, because although there are similarities between the productive dynamics, the territories have natural specificities that differentiate between SAFs established in open fields (type A), in terra firme areas, and those established in flooded forests (type F). The decision to establish and disseminate SAFs in family farming is also conditioned by socio-economic factors: production must meet both the family's food needs and market demand, especially at a local level.